The Relationship Between Testosterone Levels and the Severity of Lower Urinary Tract Symptoms : A Comprehensive Systematic Review - Muhammad Zul Fahmi; Cut Dessia Zulda Muthia (International Medical Journal Corp. Ltd, 2026)
Introduction: The relationship between testosterone levels and lower urinary tract symptoms (LUTS) in men remains controversial, with conflicting evidence from observational studies and interventional trials. This systematic review aims to comprehensively evaluate the association between testosterone levels and LUTS severity, and to assess the effects of testosterone replacement therapy (TRT) on urinary symptoms. Methods: We systematically screened studies involving adult male participants with LUTS assessment using validated instruments (IPSS, AUA-SI) and testosterone measurement via validated laboratory methods. Eighty studies comprising randomized controlled trials, observational registry studies, and cross-sectional analyses were included. Results: Cross-sectional studies showed inconsistent baseline associations between testosterone levels and LUTS severity, with some demonstrating significant negative correlations (r=-0.334, p=0.031) (21) while large-scale trials found no relationship (1,3,4). However, interventional studies consistently demonstrated that long-term TRT significantly improved LUTS. In registry studies of up to 16 years, mean IPSS decreased from 7.0±3.5 to 1.5±2.0 in treated men versus worsening from 4.9±2.0 to 14.3±5.3 in controls (p<0.0001) (5). Improvements were observed independent of prostate size (6,9) and were particularly pronounced in men with metabolic comorbidities, including type 2 diabetes (7) and obesity (59). Mechanistic studies identified effects on bladder function (44), inflammation reduction (17,32), and sleep improvement (27) as potential mediators. Effect modifiers included baseline testosterone levels, prostate size, metabolic status, and treatment duration exceeding 6 months. Discussion: The heterogeneous findings can be reconciled by recognizing that severe testosterone deficiency (<300 ng/dL) contributes to LUTS through multiple mechanisms, and restoration to normal levels with adequate treatment duration produces clinically meaningful benefits. The saturation model (75) explains why variations within normal range show no association. Benefits are maximized in men with documented hypogonadism, metabolic comorbidities, and moderate-to-severe baseline symptoms. Conclusion: Testosterone replacement therapy significantly improves LUTS in hypogonadal men, particularly those with metabolic comorbidities, with benefits requiring sustained treatment beyond 6 months. Patient selection based on documented testosterone deficiency and symptom severity optimizes therapeutic outcomes.